2015
DOI: 10.3233/bme-151284
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study on the flexural strength and compressive strength of four resin-modified luting glass ionomer cements

Abstract: Abstract. The purpose of this study is to compare the differences in flexural strength and compressive strength between four resin-modified luting glass ionomer cements that are commonly used in clinics. Furthermore, this study investigates the influence of curing mode on the flexural strength and compressive strength of dual-cured resin-modified glass ionomer cements. Initially, flexural strength and compressive strength test specimens were prepared for RL, NR, GCP, and GCC. The RL group and NR group were cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…In previous studies, the compression strength of RMGICs were found to be between 67.61 and 218.46 MPa. [10][11][12][13] According to ISO (International Standards Organization) standards, the materials are considered to be reliable if they have a compressive strength above 130 MPa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the compression strength of RMGICs were found to be between 67.61 and 218.46 MPa. [10][11][12][13] According to ISO (International Standards Organization) standards, the materials are considered to be reliable if they have a compressive strength above 130 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the flexural strength values of RMGICs are reported to be between 18.203 and 83.1 MPa. 10,13,15 The minimum flexural strength requirement for of occlusal restorations was stated as 80 MPa by the ISO standards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compressive strength is an indirect measure of bonding and strength of the material [11,12]. It is an important property that may affect clinical performance [13]. This factor plays an important role in the treatment of functional perforations where cements are directly exposed to occlusal forces [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nivo značajnosti je određen kao p < 0,05. DISKUSIJA KČ je indirektna mera vezivanja i čvrstoće materijala [11,12] i važno je svojstvo koje može uticati na kliničke performanse materijala [13]. Ovaj faktor igra važnu ulogu u tretmanu furkacionih perforacija, gde su cementi direktno izloženi delovanju okluzalnih sila [14].…”
Section: Ispitivanje Kompresivne čVrstoće Kalcijum-silikatnih Cemenataunclassified